MODELING THE IMPACT OF WEAR ON SEALING SURFACE STRESS IN TUBING JOINTS - SAI KUMAR, TALLOORI; SURESH, BHUKYA; KRISHNA, YANAKAPATI; PRASAD, V. DURGA (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Tubing joints lose their integrity and tightness with aging. Here, we investigate the features of the stress distribution on the sealing surface and suggest a novel joint wear calculation technique based on the numerical cutting methodology. To determine the stress distribution on the sealing surface, a finite element model of a worn tubing junction subjected to complicated stresses was constructed and validated. The analysis of the stress distribution on the sealing surface provided insight into the failure mechanism of a worn tubing connection as well as the impacts of interior wear on the joint. The findings demonstrated that as internal wear depth grew, the contact stress of the worn portion of the sealing surface decreased. The maximum contact stress in the worn area is 35.5% lower in the axial direction and 27.3% lower in the circumferential direction of the sealing surface compared to an unworn joint when the internal wear depth reaches 3.0 mm. When the exterior wear of the joint is 3.0 mm or less, the sealing surface stress distribution of the joint is nearly identical to that of a new joint. Controlling internal wear during operation is therefore more important than preventing exterior wear because internal wear has a greater impact on the sealing surface's stress characteristics than external wear. The sealing belt features a wide range of wear depths and two wear types, with a generally constant width at the sealing surface. The quality of the tubing connection seal is maintained by doing this. tube junction, sealing performance, contact stress, wear modeling, and numerical cutting process.